Reducing Academic Stress through Exercise: A Study of High School Students - Yulifah Salistia Budi; Sholihin Sholihin; Shabrina Zhafira Salsabila (Media Ilmiah Kesehatan Indonesia, 2026)
Current technological advancements have led to teenagers spending more time sitting and playing with smartphones compared to engaging in physical activities. Physical exercise is a planned and organized activity aimed at improving physical condition. One of the benefits of physical exercise is its ability to reduce stress levels. Teenagers often engage in physical exercise as a strategy to manage stress. This study aims to explore the relationship between exercise habits and stress levels among students at SMAN 1 Giri Taruna Bangsa, Banyuwangi, in 2024. This research utilized a correlational study with a cross-sectional approach. A total of 66 grade XI students were selected through cluster random sampling. The instruments used were the Exercise Habit Questionnaire and the Academic Stress Scale (ASS) questionnaire. The collected data were analyzed using the Spearman Rank correlation in IBM SPSS Statistics v.25. Most respondents reported irregular exercise habits, with 40 respondents (61%) falling into this category. The majority of respondents experienced moderate stress, with 30 respondents (45%) reporting this level. The Sig. 2-tailed value of 0.000 (p < 0.05) indicates a significant relationship between exercise habits and stress levels. Regular exercise provides optimal benefits for the respondents, such as reducing stress. Regular physical activity can be incorporated into daily schedules to achieve these benefits.